Olam significantly reduces food loss and greenhouse gas emissions based on CCAFS-Wageningen Food & Biobased Research (WFBR) measurement analyses and ACE calculator results - CGIAR Research Program on Climate Change, Agriculture and Food Security (2020)
Olam used CCAFS-Wageningen Food & Biobased Research (WFBR) science to identify threshing and harvesting as hotspots for food losses in rice farming communities. Using the Agro-Chain greenhouse gas Emissions (ACE) calculator, mechanizations of these operations were identified interventions with strong positive effects on food loss reduction (14%) and greenhouse gas emissions reduction (15%), 117 kton CO2e for all Nigerian rice farmers supplying to Olam.